So(2,1) Lie algebra and the Green's functions for the conditionally exactly solvable potentials - Dutra, Alvaro de Souza [UNESP]; Boschi-Filho, Henrique (American Physical Society (APS), 1994)
The Green's functions of the recently discovered conditionally exactly solvable potentials are computed. This is done through the use of a second-order differential realization of the so(2,1) Lie algebra. So we present the dynamical symmetry underlying the solvability of such potentials and show that they belong to a general class of solvable and partially solvable potentials. © 1994 The American Physical Society.